Influence of suckling and continuous cow-calf association on the resumption of post-partum ovarian function in Bos indicus cows monitored by plasma progesterone profiles - Mukasa-Mugerwa, E.; Tegegne, Azage; Franceschini, R. (1991)
Assesses the effect of cow-calf association and continuous suckling on the resumption of oestral activity; and monitors the temporal patterns of plasma progesterone during the post-partum period in grazing Ethiopian Small East African Zebu cows under uncontrolled mating.